2006
DOI: 10.1007/s00134-006-0073-1
|View full text |Cite|
|
Sign up to set email alerts
|

Heat and moisture exchangers and heated humidifiers in acute lung injury/acute respiratory distress syndrome patients. Effects on respiratory mechanics and gas exchange

Abstract: Reducing dead space with the use of HH decreases PaCO2 and more importantly, if isocapnic conditions are maintained by reducing Vt, this strategy improves respiratory system compliance and reduces plateau airway pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 38 publications
3
31
0
1
Order By: Relevance
“…This intervention has been shown to be effective to reduce PaCO 2 while ventilating ARDS patients with a low Vt strategy [11,21]. Although some authors have suggested that HMEFs should be avoided during ventilation with a Vt of 6 ml/kg [22], this is not a standard practice, and furthermore, several ICUs keep using HMEFs in mechanically ventilated ARDS patients [23,24]. In the present study we kept the HMEF during ventilation with Vt 6, as was the usual practice in our ICU, but we removed it during ventilation with Vt 4.…”
Section: Discussionmentioning
confidence: 99%
“…This intervention has been shown to be effective to reduce PaCO 2 while ventilating ARDS patients with a low Vt strategy [11,21]. Although some authors have suggested that HMEFs should be avoided during ventilation with a Vt of 6 ml/kg [22], this is not a standard practice, and furthermore, several ICUs keep using HMEFs in mechanically ventilated ARDS patients [23,24]. In the present study we kept the HMEF during ventilation with Vt 6, as was the usual practice in our ICU, but we removed it during ventilation with Vt 4.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] 4.3 When providing humidification to patients with low tidal volumes, such as when lung-protective ventilation strategies are used, HMEs are not recommended because they contribute additional dead space, which can increase the ventilation requirement and P aCO 2 . 25 4.3.1 Artificial airway dead-space reduction allows a significant P aCO 2 reduction that is independent of any respiratory mechanical changes.…”
Section: 2mentioning
confidence: 99%
“…Many other strategies have also been developed to decrease hypercapnia at the bedside, such as increases in respiratory rate [8], use of active humidifiers [9] and the tracheal gas insufflation [10] or aspiration of dead space [11]. At bedside, the dead space could be calculated using the Enghoff modification of the Bohr equation.…”
Section: Introductionmentioning
confidence: 99%